The Fate of Marine Litter in Semi-Enclosed Seas: A Case Study of the Black Sea - Stanev, Emil V.; Ricker, Marcel (Frontiers in Marine Science, 2019)
The accumulation patterns of floating marine litter (FML) in the Black Sea and the stranding locations on coasts are studied by performing dedicated Lagrangian simulations using freely available ocean current and Stokes drift data from operational models. The low FML concentrations in the eastern and northern areas and the high concentrations along the western and southern coasts are due to the dominant northerlies and resulting Ekman and Stokes drift. No pronounced FML accumulation zones resembling the Great Pacific Garbage Patch are observed at time scales from months to a year. The ratio of circulation intensity (measured by the sea level slope) to the rate of the temporal variability of sea level determines whether FML will compact. This ratio is low in the Black Sea, which is prohibitive for FML accumulation. It is demonstrated that the strong temporal variability of the velocity field (ageostrophic motion) acts as a mixing mechanism that opposes another ageostrophic constituent of the velocity field (spatial variability in sea level slope, or frontogenesis), the latter promoting the accumulation of particles. The conclusion is that not all ageostrophic ocean processes lead to clustering. The short characteristic stranding time of ~20 days in this small and almost enclosed basin explains the large variability in the total amount of FML and the low FML concentration in the open ocean. The predominant stranding areas are determined by the cyclonic general circulation. The simulated distribution of stranded objects is supported by available coastal and near-coastal observations. It is shown that the areas that were the most at risk extend from the Kerch Strait to the western coast.